Revisiting florivory: an integrative review and global patterns of a neglected interaction. Issue 1 (27th August 2021) - Boaventura, Maria Gabriela; Villamil, Nora; Teixido, Alberto L.; Tito, Richard; Vasconcelos, Heraldo L.; Silveira, Fernando A. O.; Cornelissen, Tatiana
Summary: Florivory is an ancient interaction which has rarely been quantified due to a lack of standardized protocols, thus impairing biogeographical and phylogenetic comparisons. We created a global, continuously updated, open‐access database comprising 180 species and 64 families to compare floral damage between tropical and temperate plants, to examine the effects of plant traits on floral damage, and to explore the eco‐evolutionary dynamics of flower–florivore interactions. Flower damage is widespread across angiosperms, but was two‐fold higher in tropical vs temperate species, suggesting stronger fitness impacts in the tropics. Flowers were mostly damaged by chewers, but neither flower color nor symmetry explained differences in florivory. Herbivory and florivory levels were positively correlated within species, even though the richness of the florivore community does not affect florivory levels. We show that florivory impacts plant fitness via multiple pathways and that ignoring this interaction makes it more difficult to obtain a broad understanding of the ecology and evolution of angiosperms. Finally, we propose a standardized protocol for florivory measurements, and identify key research avenues that will help fill persistent knowledge gaps. Florivory is expected to be a central research topic in an epoch characterized by widespread decreases in insect populations that comprise both pollinators and florivores.